(untitled) (Research, Society and Development, 2022)
Vocal health is considered an important factor in the health and quality of life of teaching professionals who use the voice as a work tool. Educational actions allow strengthening health promotion, always highlighting preventive aspects for good vocal quality. In this perspective, this study was aimed at analyzing the perception of teachers about the Program Taking care of the Master, developed in municipal schools in Sobral-CE. Qualitative research was used as the most appropriate approach, and action research as a methodological path. The research universe consisted of eight permanent active teachers in the Municipal Public Teaching System of Sobral, who participated in all the workshops of the program Taking care of the Master. The data were obtained through semi-structured interviews conducted with the teachers participating in the research, and the content analysis was anchored in the thematic analysis. The results confirmed that the program Taking care of the Master enabled major changes in the perception of teachers about vocal health. Therefore, it is essential to implement courses, lectures and workshops, consultations with the aim of developing the vocal knowledge of the teacher as a requirement for his/her health.